Replication of damaged DNA - Upton, Amy Louise (2009)
DNA is under constant attack from numerous damaging agents and our cells deal with thousands of lesions every day. With such constant damage it is inevitable that the template will not be completely cleared of lesions before the replication complex arrives. The consequences of the replisome meeting an obstacle will depend upon the nature of the obstacle. I have focussed upon replication in Escherichia coli and the effect of UV-induced lesions, which would block synthesis by the replicative polymerases. It is accepted that a UV lesion in the lagging strand template can be bypassed by the replisome complex, but the consequences of meeting a lesion in the leading strand template remain unclear. A lesion in the leading strand template could block replisome progression and the fork might require extensive processing in order to restart replication. However, it has also been proposed that the replisome could progress past these lesions by re‐priming replication downstream and leaving a gap opposite the lesion.